Can science education help to build a sustainable society? - Barraza, Laura; Castaño, Carolina (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
In this article we present a critical description regarding some of the guidelines that we consider are needed within education at university level to guide and transform the educative system towards an education for sustainability. To speak about sustainability we need to consider restructuring the teaching programs at all educative levels. For this, we discuss the relevance in adapting the six dimensions of the content-based knowledge towards sustainability issues, as well as the implications that the concept of sustainability has for our views, attitudes and actions. Transformative learning theories and pedagogical strategies for teaching science which could be useful for educating for sustainability and which could encourage changes in the attitudes of those who will become future teachers, such as the 5 “E” model which promotes critical and reflexive thinking are also discussed. We propose an educative model for teaching about sustainability with four basic epistemological elements: a multicultural education, an education for the future, a holistic education, and, a participatory education.